Unfolded protein response in a Drosophila model for retinal degeneration. - Ryoo, H.D.; Domingos, P.M.; Kang, M.J.; Steller, H. (The EMBO Journal, 2007)
Stress in the endoplasmic reticulum (ER stress) and its cellular response, the unfolded protein response (UPR), are implicated in a wide variety of diseases, but its significance in many disorders remains to be validated in vivo. Here, we analyzed a branch of the UPR mediated by xbp1 in Drosophila to establish its role in neurodegenerative diseases. The Drosophila xbp1 mRNA undergoes ire-1-mediated unconventional splicing in response to ER stress, and this property was used to develop a specific UPR marker, xbp1-EGFP, in which EGFP is expressed in frame only after ER stress. xbp1-EGFP responds specifically to ER stress, but not to proteins that form cytoplasmic aggregates. The ire-1/xbp1 pathway regulates heat shock cognate protein 3 (hsc3), an ER chaperone. xbp1 splicing and hsc3 induction occur in the retina of ninaE(G69D)-/+, a Drosophila model for autosomal dominant retinitis pigmentosa (ADRP), and reduction of xbp1 gene dosage accelerates retinal degeneration of these animals. These results demonstrate the role of the UPR in the Drosophila ADRP model and open new opportunities for examining the UPR in other Drosophila disease models.